TIPOLOGI PEMIKIRAN PENDIDIKAN ISLAM (Telaah Pemikiran Imam Suprayogo Dan Azyumardi Azra) - Baydah Ansoro; Mohammad Ali Murtada (LP2M IAI Miftahul Ulum Pamekasan, 2022)
Law or a provision will always run dynamically by the movement of time and changes in place. Because the era of globalization coldly demands changes in all lines and aspects. This is a reality clause from the development of science that continues to advance plus technology that is getting faster towards unlimited sophistication. Islamic education as part of the rolling of changes that occur is required to always think dynamically, not stagnate, to keep up with changes that are always bound to happen, but of course they must consistently rely on qot'iy arguments (al-Qur'an and al-Hadith) as the main source and it is also possible to remain proactive and responsive in chess in this era. In this case, it seems as if picking up a wild ball that continues to roll Imam Suprayogo and Azyumardi Azra with their broad insight spawned brilliant ideas and are expected to be able to color and bring significant changes, especially in Islamic education both theoretically and practically. The purpose of this paper is to describe the views of Imam Suprayogo and Azyumardi Azra and identify and analyze their way of thinking in relation to Islamic education.